A (Im)possibilidade de utilização de inquéritos e ações penais em curso como fundamento para a decretação de prisão preventiva para a garantia da ordem pública sob a ótica do garantismo penal - OLIVEIRA, Daniel Lima de (2021)
This course conclusion work, through bibliographic and documentary procedure, aims to discuss the (im)possibility of using investigations and criminal proceedings in progress as a basis for the decree of pre-trial detention for the guarantee of public order under Luigi Ferrajoli's theory of penal guarantism in the light of the constitutional principle of presumption of innocence. Tries to delineate also about the problem of the indeterminate concept of “public order” and the possibility of creating the figure of the enemy, already criticized by Eugenio Raúl Zaffaroni. The hypothetical-deductive approach method was used.